Studying Factors in the Utilization of Sansevieria stuckyi God.-Leb. Fibers to Create Products with Environmentally Friendly Processes - Sudakan Yabdee; Thanate Piromgarn; Sirisyos Kijmongkolvanich; Songwut Egwutvongsa (International Journal of Sustainable Development and Planning, 2024)
The objective of this research was to study the utilization and physical properties of Sansevieria stuckyi God.-Leb.This was a mixed-methods study conducted using a structured questionnaire having a high reliability score (Cronbach's alpha = 0.936).According to the exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), four significant factors were revealed, e.g., 1) utility, 2) perception, 3) sales motivation, and 4) eco-friendly materials.These factors affect the efficiency in the creation of fiber-based textile products.The results of this research generated a process for the recycling of numerous local wastes for economic value added of the involved communities and establishment of the guidelines on utilizing Sansevieria stuckyi God.-Leb.to create textile products with an eco-friendly process.This will generate a body of knowledge and understanding of how to develop textile products that meet consumer needs.In addition, the results of this research will motivate textile product designers to apply their local plants in textile product creation in order to meet the needs of community inhabitants appropriately and to demonstrate their collective responsibility for the global environment.
Keywords: Medicinal Plant Research